Exploring English Language Teachers’ Experiences on Extensive Reading: An Interpretive Inquiry - Sharma, Janaki; Gnawali, Laxman (The Harvest, 2025)
This study explores teachers' perspectives and challenges they face in implementing Extensive Reading (ER) activities. It also explores whether extensive reading could enhance students' motivation to read in English and foster positive attitudes toward reading in English. The study involved two novice and two experienced teachers from private schools in Kathmandu. Semi-structured interviews were conducted with teachers. The findings show that while teachers recognized the benefits of ER and supported its implementation, challenges like tough books, lack of libraries, and lack of knowledge about the selection of level-appropriate books for students. The study suggests that for ER to be successful, a coordinated effort and a shift in attitudes among students, teachers, and other stakeholders are essential. This study further attempts to contribute to the growth of future research on extensive reading in Nepal.